2018
DOI: 10.1177/2325967118781579
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Specific Morphologic Variations of Capital Femoral Epiphysis Growth in Children and Adolescents Without Hip Disorders

Abstract: Background:Understanding the development of the capital femoral epiphysis is essential to identify pathologic variations that may lead to cam morphology.Purpose/Hypothesis:The purpose of this study was to investigate the development of the capital femoral epiphysis during childhood and adolescence, with specific morphologic analysis of the peripheral growth and the metaphyseal surface of the growth plate. We hypothesized that age- and sex-dependent morphologic variations of the peripheral growth (cupping) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 37 publications
4
53
0
Order By: Relevance
“…We found that the stabilizing role of the tubercle is primarily at early stages of adolescence when the tubercle is prominent, and the peripheral cupping is absent or underdeveloped . The age‐related changes in epiphyseal surface morphology shifts the loading dynamics of the epiphysis in a way that the epiphyseal cupping will become a more important stabilizer of the epiphysis in later stages of adolescence.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…We found that the stabilizing role of the tubercle is primarily at early stages of adolescence when the tubercle is prominent, and the peripheral cupping is absent or underdeveloped . The age‐related changes in epiphyseal surface morphology shifts the loading dynamics of the epiphysis in a way that the epiphyseal cupping will become a more important stabilizer of the epiphysis in later stages of adolescence.…”
Section: Discussionmentioning
confidence: 83%
“…Previous investigations about morphologic variations of the capital femoral epiphysis have described that the epiphyseal tubercle reduces while the peripheral cupping increases during the period of rapid adolescent growth . The epiphyseal tubercle has been suggested to act as a keystone stabilizer of the capital femoral epiphysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations